Implementation of aquaponics as an alternative income for CATFISH farmers group in Gajah Village, Jombang - Anggi Indah Yuliana; Mohamad Nasirudin; Rohmat Hidayat (Universitas Muhammadiyah Magelang, 2024)
The catfish hatchery business practices carried out by the CATFISH fish farmers group in Gajah Village, Ngoro District, Jombang Regency produce waste that has the potential to pollute the aquatic environment around the cultivation location. On the other hand, catfish waste can be used as an alternative source of nutrients for plants. Therefore, this community service activity aims to improve the knowledge and skills of partners regarding the aquaponic system as an alternative business diversification that increases cultivator income and reduces catfish waste pollution to the environment. The methods and stages in community empowerment activities include: (1) identifying partner needs, (2) introducing technology to partners through socialization and training, and (3) operational technology assistance. The socialization and training activities had an impact on increasing the knowledge and skills of partners regarding aquaponics as an alternative income for catfish hatchery businesses.